Percutaneous Venoarterial Extracorporeal Membrane Oxygenation for Refractory Cardiogenic Shock Is Associated with Improved Short- and Long-Term Survival. Issue 4 (July 2016) - Hryniewicz, Katarzyna; Sandoval, Yader; Samara, Michael; Bennett, Mosi; Cabuay, Barry; Chavez, Ivan J.; Seatter, Susan; Eckman, Peter; Zimbwa, Peter; Dunn, Aaron; Sun, Benjamin
Abstract : Mortality due to refractory cardiogenic shock (RCS) exceeds 50%. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) has become an accepted therapy for RCS. The aim of our study was to evaluate outcomes of patients with RCS treated with percutaneous VA-ECMO (pVA-ECMO). Retrospective review of patients supported with VA-ECMO at our institution in 2012–2013. Clinical characteristics, bleeding, vascular complications, and outcomes including survival were assessed. A total of 37 patients were supported with VA-ECMO for RCS. The majority of VA-ECMO (76%) was placed in the catheterization laboratory. Nearly half (49%) of the patients presented with acute myocardial infarction. Seven patients (19%) underwent insertion of pVA-ECMO in the setting of cardiopulmonary resuscitation with mechanical chest compression device. Median duration of support was 5 days. Index hospitalization, 30-day, and 1-year survival were 65%, 65%, and 57%, respectively. Survival rate for discharged patients was 87.5% with a median follow-up of 450 days. Refractory cardiogenic shock supported with pVA-ECMO is associated with an improved survival in patients with a traditionally poor prognosis.